Análise genética de populações naturais de Polybia paulista Ihering, 1896 (Hymenoptera: Epiponini) - Alves, Davis João (2011)
The social wasp Polybia paulista (Hymenoptera: Epiponini) is an important agent pollinator of the cultivated plants, as well as a natural predator of pests, due to its herbivorous-carnivorous food habits, easily found nidifying in urban areas and built environments. Due to its economic and ecological importance, the present work used molecular markers to characterize the isoenzymatic system of the esterases in the several stages of the ontogenic development of the insect, showing ten esterases (EST - nº E.C. 3.1.1.1) in the electrophoretic analysis of extracts of head/thorax of adults, pupae, prepupae and larvae, numerically designated according to the electrophoretic mobility in EST-1 to the one that presented the highest mobility and EST-10 to the one that presented the lowest mobility. EST-9 was classified as β-esterase, while the others were classified as αβ-esterases. To analyze the populations of P. paulista, ten nests were collected in three municipalities of the state of Paraná (Maringá, Umuarama and Maria Helena, being the latter two considered as a single population) and analyzed through starch gel isoenzyme electrophoresis, showing 4 enzymatic systems: malate dehydrogenase (MDH - nº E.C. 1.1.1.37), isocitrate dehydrogenase (IDH - nº E.C. 1.1.1.42), glyceraldehyde 3-phosphate dehydrogenase (G3PDH - nº E.C. 1.1.1.8) and phosphoglucomutase (PGM - nº E.C. 2.7.5.1). Analyses using polyacrylamide gel electrophoresis were also performed to indicate the esterases. The results showed fourteen isoenzymatic loci, of which five were polymorphic (35,71%). The genetic diversity was calculated using the Shannon index (I), and presented an average value of 0.2416, considering all the individuals analyzed; considering each single population, the values detected were close (0.2321 to the population of Maringá and 0.2389 to the population of Umuarama). The fixation index calculated to the populations was positive value (0.2747), indicating an excess of homozygotes in the population. The level of differentiation presented a low value (0.0352), indicating that the populations are not differentiated.The calculated values of Nei's genetic distance and identity (1978) were 0.9862 and 0.0139, respectively, confirming the fact that these populations have a significant genetic proximity.